POLITENESS IN THE THREADS @PRATIWI.CRISTIN - Nurmaulida, Dela; Rohayati, Nia; Munir, Sirojul (Diksatrasia : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
The Study aims to describe and analyze the characteristic of language politeness in @pratiwi.cristin’s Threads post, which highlight social and education issues, and to link them with the development of factual argumentative writing materials based on cognitive neuroscience. Research employs a qualitative descriptive approach using literature review, documentation, and observation techniques. The finding reveal that the threads post politeness characteristic aligned with Leech’s maxims, such as tact, approbation, sympaty, generosity, agreement, and modesty. Factor such as topic, delivery style, and social context significantly influence the formation of polite utterances. The result serve as a foundation for developing contextual and relevant alternative teaching materials, particularly for argumentative writing instruction at the senior high school level. The use of digital media platforms like Threads proves effective in increasing students ‘engagement and critical thinking skills. Although challenges remain in integrating cognitive neuroscience into classroom pratices, this study offers innovative insight into design of digital-based learning materials that are timely and reflective.